Schools In the Fatwa of the National Sharia Council of the Indonesian Ulama Council (Analysis of Mudharabah, Musyarakah and Murabahah) - Aicha Azdina Adly Fesya; Acme Admira Arafah (Program Pascasarjana UIN Sumatera Utara Medan, 2018)
There are different types of mazhab adopted in the Fatwa of DSN-MUI related to musharaka, mudaraba and murabaha. In the fatwa of the DSN-MUI on Musharaka, both in terms of material content and applicative, if observed substantially, it tends more towards Hanafi's madhhab. However, the DSN-MUI fatwas about Mudharabah were different, the DSN-MUI fatwa is mostly to be taken and agreed on a legal basis by Syafi'i as its fatwa. While the DSN-MUI fatwa on Murabaha, the legal basis and the determination substance of the fatwa material, more relies on the same proportion as the four madzhab known so far. Thus, in giving the DSN fatwa to be implemented in Indonesia, the Indonesian Council of Ulama's had to refer to the various madhhab. Although there are several provisions that are adapted to the conditions of the times, still fatwas do not violate the general rules that have been submitted by the first madhhab.